TU4.4 'Nurse led Colorectal 2ww clinic': Impact on early assessment and faster diagnosis of colorectal cancer. (9th August 2022) - Chowdhury, Ashim; Shrestha, Anuj; Williams, Larissa; Aravind, Biju; Basnyat, Pradeep; Shrestha, Ashish
Abstract: Background: Colorectal cancer (CRC) is the second most common cancer death in the UK with a 5-year relative survival rate is 57%, which has improved over the last 30 years. Early detection of the cancer has a great impact on its prognosis. In our large district general hospital, we receive GP 2 week pathway referrals for suspected CRC with an average monthly referral of 726. Therefore, the aim of this study is to assess if recently introduced nurses led colorectal rapid access clinic has any impact on early assessment that can facilitate faster diagnosis. Method: A retrospective analysis of a prospectively collected data of the patient referred through a 2-week colorectal clinic pathway from outpatient referral system, was carried out from April, 2021 to November, 2021. Patient feedback and clinician advice and guidance were also evaluated in the same period. Result: A total of 900 patients were reviewed in our Nurse led clinic with CRC detection rate of 2% approximately. Final diagnosis of cancer been made within the 28th day. Increment of 21% was seen in referrals per month. Optimal slots of 195/week are required but the nurse led clinic capacity is only 40/week. Despite the increased referral, patients are being provided with results within day 13 with positive feedback from the patients. Conclusion: Despite of overwhelmed referrals, final diagnosis is provided within 28 days. Nurse Led Colo-rectal Clinic could be the answer to relieving the capacity, financial pressures and providing high quality safe patient care for our already strained NHS.